Student Performance as Social Worker inside Child Care Services Practice at Vocational Social Work Department - Yosi Agustina; Yoyoh Jubaedah; Nenden Rani Rinekasari (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2025)
The research entitled